Former Yugoslav Republic of Macedonia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews economic developments in the Former Yugoslav Republic of Macedonia during 1994-98. In 1994-95, the authorities reasserted control over monetary policy, stabilized the exchange rate, and undertook a substantial fiscal adjustment. As a result, price stability was restored by 1996 and the decline in output was arrested. Programs for recapitalizing banks and accelerating the process of enterprise adjustment and privatization began in 1995. In 1996, the economy started to pick up, but a surge in industrial output in late 1996, partly reflecting the restarting of the oil refinery, could not be maintained.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet